2021
DOI: 10.3389/fonc.2021.691115
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors and Methylation Drive Prognostic miRNA Dysregulation in Hepatocellular Carcinoma

Abstract: Many dysregulated microRNAs (miRNAs) have been suggested to serve as oncogenes or tumor suppressors to act as diagnostic and prognostic factors for HCC patients. However, the dysregulated mechanisms of miRNAs in HCC remain largely unknown. Herein, we firstly identify 114 disordered mature miRNAs in HCC, 93 of them are caused by dysregulated transcription factors, and 10 of them are driven by the DNA methylation of their promoter regions. Secondly, we find that seven up-regulated miRNAs (miR-9-5p, miR-452-5p, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…The dysregulation of miRNAs is common in cancers and is caused by various mechanisms, including mutations involving miRNA loci, epigenetic silencing, and transcription factor dysregulation [ 6 , 7 , 8 , 9 , 10 ]. Through sRNA sequencing, we confirmed that hsa-miR-100-5p is downregulated in several HCC cell lines, which suggests a close association between hsa-miR-100-5p dysregulation and HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of miRNAs is common in cancers and is caused by various mechanisms, including mutations involving miRNA loci, epigenetic silencing, and transcription factor dysregulation [ 6 , 7 , 8 , 9 , 10 ]. Through sRNA sequencing, we confirmed that hsa-miR-100-5p is downregulated in several HCC cell lines, which suggests a close association between hsa-miR-100-5p dysregulation and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small endogenous single-stranded non-coding RNAs that have been recognized as playing essential roles in cancer prognosis by regulating a wide range of biological processes, typically via sequence-specific RNA-RNA interactions [ 5 , 6 ]. Due to various mutations, miRNAs are heavily dysregulated in cancer cells, leading to the dysregulation of multiple protein-coding oncogenes [ 6 , 7 , 8 , 9 , 10 ]. miRNAs are crucial regulators in the development and progression of HCC [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the AUC values of miRNA-452-5p, miRNA-5589-5p, miRNA-5589-3p, and miRNA-4661-5p in the early diagnosis of HCC were 0.830, 0.879, 0.838, and 0.725, respectively. Moreover, the four miRNAs were differentially expressed in only one or two types of cancer with good specificity, which might be used as the early diagnostic biomarkers for HCC [ 62 ]. In addition, Huang et al found that miRNAs might also serve as the diagnostic biomarkers for lung metastasis in HCC patients, and the combination of multiple miRNAs had better performance than a single miRNA.…”
Section: Mirnas and Cancer Diagnosis And Prognosismentioning
confidence: 99%
“…For instance, miR-1292-5p and miR-1301-3p helped regulate cell proliferation and epithelial–mesenchymal transformation (EMT) of common tumors in general surgery (e.g., thyroid cancer and gastric cancer). , miR-3614-5p could act as an antiviral and a regulator of human primary macrophages, thereby controlling dengue viral replication . Furthermore, miR-5589-3p could be one of the vital methylation drivers and transcription factors in liver cancer …”
Section: Introductionmentioning
confidence: 99%
“…19 Furthermore, miR-5589-3p could be one of the vital methylation drivers and transcription factors in liver cancer. 20 With the development of modern medical technology, researchers have more stringent requirements for the molecules that can be used for visual observation. Many optical nanoprobes are available, including organic smallmolecule dyes, fluorescent proteins, and inorganic quantum dots, 21−24 which are used as the primary carrier tools for biomedical imaging and play an essential part in basic scientific research; clinical laboratory examination; and interpretation, diagnosis and prognostic evaluation of diseases.…”
Section: ■ Introductionmentioning
confidence: 99%